Análisis espacial y temporal de Q-Coda en el Piedemonte Llanero (Colombia) - Duran Juan P.; Vargas Carlos A.; Briceño Luis A. (Earth Sciences Research Journal)
The space-time variation of the parameter of attenuation Q-Coda in a sector of the Piedemonte L1anero was studied using the Coda waves. The estimation ofthe attenuation of the amplitude of coda is calculated by means of the Model of simple Isotropic. Dispersion of Sa to, from earthquakes seismograms happened in the region from September 1993 to June 2002. Following the methodology used by Aki and Chouet (1975), they analyzed seismograms in four centered bands to 1.5,3,6 and 12 Hertz with its corresponding bandwidths of 1, 2, 4 and 8 Hertz. And by regression to linear calculated the value of Qc to I Hertz. From the expression proposed by Puli to model the amplitude of the waves coda by means of ellipses, this expression was extended to calculate the space variation ofthe Qc-I, (anelastic tomography). And by inverse square minimums, the value of attenuation for each cell of the three-dimensional model was calculated. Their results were correlated with the regional tectonic frame showing that when the attenuation increases by depth, it corresponds to zones with Tectonics of thick skin and, on the contrary, where the attenuation diminishes by depth, it corresponds to zones with Tectonics of thin skin. On the other hand, the temporary variation of minimum values ofQc (maximum attenuations) was correlated to qualitatively earthquakes of magnitude greater to 3,5 and, in addition, the temporary distribution ofQc was quantified by dimension fractal showing that the grouping of the minimum values ofQc increases before ocurring a main event and its grouping decreases after occurring the main event. La variación espacial y temporal del parámetro de atenuación Q-Coda en un sector del Piedemonte Llanero es estudiada usando las ondas Coda. La estirnación de la atenuación de la amplitud de la coda se calcula por medio del Modelo de Dispersión Isotropica Simple de Sato, a partir de sismogramas de sismos que ocurrieron en la región entre septiembre de 1993 a junio 2002. Siguiendo la metodología empleada por Aki y Chouet (1975), se analizaron los sismogramas en cuatro bandas centradas a 1.5, 3, 6 y 12 Hz con sus respectivos anchos de banda de 1, 2, 4 y 8 Hz. Por regresión linear se cálculo el valor de Qc a 1 Hz. A partir de la expresión propuesta por Puli para modelar las amplitudes de las ondas coda por medio de elipses, se amplio esta expresión para calcular la variación espacial del Qc-l, para un medio tridimensional (tomografía anelástica). Y por medio de inversión por mínimos cuadrados se calculó el valor de atenuación para cada celda del modelo tridimensional. Los resultados se correlacionaron con el marco tectónico regional encontrando que cuando la atenuación aumenta con la profundidad, corresponde a zonas con tectónica de piel gruesa y por el contrario, cuando la atenuación disminuye con la profundidad, corresponde a zonas con tectónica de piel delgada. Por otro lado, la variación temporal de los mínimos valores de Qc (máximas atenuaciones) se correlacionó cualitativamente con sismos de magnitud mayor de 3.5 y, además, se cuantificó la distribución temporal de Qc por medio de la dimensión fractal, mostrando que la agrupación de los valores mínimos de Qc aumenta antes de la ocurrencia de un evento principal y decrece su agrupación después de la ocurrencia del evento principal.